PENINGKATAN KINERJA GURU DAN HASIL BELAJAR IPA BERBASIS INKUIRI DI KELAS VB SDN 73 - Indrawati, Lies (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Science learning that was taught merely as a product has resulted in low students’ achievement. Therefore, a classroom action research was conducted to know the improvement of teacher’s performance and students’ achievement through inquiry-based science. The subject of the research was the home teacher of 5th grade SDN 73 West Pontianak in 2016/2017. Assisted by two collaborators, teacher’s performance was observed and students’ achievement was measured. Data was collected in four phases: planning, acting, observing, and reflecting. Average score of teacher’s performance in planning inquiry based science was varied from 83 to 87 or very good. In conducting inquiry based science, average score varied from 50 to 90 or good. Students’ achievement in science as a product showed improvement in 4 meetings. Percentage of students’ mastery learning increased from 20.62 to 58.19. As a scientific attitude, in cycle 1 curiosity, logic, and responsibility increased from 0.16 to 1.02. Honesty decreased 0.09. In cycle 2, curiosity and responsibility increased from 0.01 to 0.23. Logic and honesty decreased from 0.08 to 0.12. As a process, 5 aspects of it increased in cycle 1 from 0.17 to 0.51. In cycle 2, the aspect of asking question and presenting observation data increased from 0.17 to 0.23. Aspect of observing and explaining science concept decreased from 0.09 to 0.24. Keywords: Teacher’s performance, Students’ achievement, Inquiry based science